2015
DOI: 10.1371/journal.pntd.0003768
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Antihelminthic Treatment on Vaccine Immunogenicity to a Seasonal Influenza Vaccine in Primary School Children in Gabon: A Randomized Placebo-Controlled Trial

Abstract: BackgroundHelminth infections are a major public health problem, especially in the tropics. Infected individuals have an altered immune response with evidence that antibody response to vaccination is impaired. Hence, treatment of helminth infections before vaccination may be a simple intervention to improve vaccine immunogenicity. In the present study we investigated whether a single-dose antihelminthic treatment influences antibody responses to a seasonal influenza vaccine in primary school children living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…The HPV specific IgG level titers were slightly higher in the group that underwent anti-helminth treatment compared to the group with the chronic S. mansoni infection. This finding is in accordance with a study that investigated the effect anti-helmithic treatment has on the efficacy of the influenza and Tetanus toxoid vaccine [21,40].…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cysupporting
confidence: 92%
See 1 more Smart Citation
“…The HPV specific IgG level titers were slightly higher in the group that underwent anti-helminth treatment compared to the group with the chronic S. mansoni infection. This finding is in accordance with a study that investigated the effect anti-helmithic treatment has on the efficacy of the influenza and Tetanus toxoid vaccine [21,40].…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cysupporting
confidence: 92%
“…The study provided an indication that the study subjects with chronic schistosomiasis were capable of responding to the vaccines and produced HPV specific IgG antibodies, however, after the 6 th week a decrease in IgG levels was observed. This reduced humoral response has also been observed in helminth infected subjects administered with a number of vaccines [22,[40][41][42].…”
Section: Chronic S Mansoni Infection Has No Significant Effect On Cymentioning
confidence: 57%
“…The presence of helminths was associated with poorer immunogenicity. A follow up study 22 failed to show a significant effect of albendazole on HAI response to IIV3, although the study was powered for a much higher helminth burden than observed.…”
Section: Studies Assessing Immunogenicity Of Influenza Vaccinesmentioning
confidence: 99%
“…Studies varied by study design, vaccine type (inactivated influenza vaccine, IIV3; live attenuated influenza vaccine, LAIV) and study population (Table 1). 16 were from South Africa, [11][12][13][14][16][17][18][19]23,25,[27][28][29][30][31][32] two each from Gabon 21,22 and Kenya, 20,26 and one study each from Mali 15,33 Senegal 24 and The Gambia. 33 The following study populations were identified: pregnant women (6 studies), children (6), elderly (3), HIV-Positive adults (1), healthcare workers (1) and all age groups (6).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation